Effects of a combined resistance-plyometric training program on muscular strength, running economy, and VO2peak in Division I female soccer players - Grieco, G. R.; Cortes, N.; Greska, E. K.; Lucci, S.; Onate, J. A. (The Journal of Strength and Conditioning Research, 2012)
Resistance and plyometric training programs have demonstrated consistent improvements in running economy (RE) in trained and untrained adults in the absence of improvements in maximal oxygen consumption. The purpose of this study was to investigate the effect of a 10-week combined resistance-plyometric training program on the RE and VO2max in female soccer players. Fifteen Division 1A female soccer players (age 19.0 ± 0.7 years; height 1.67 ± 0.1 m; weight 61.7 ± 8.1 kg) performed a treadmill test for VO2max and RE at the end of a competitive season (PRE) and after a 10-week training program (POST). Isometric strength was measured in knee flexion and extension. Resistance training was conducted 2 d/wk on nonconsecutive days; plyometric training was conducted separately on different nonconsecutive days. Eleven subjects were included in the PRE-POST analysis (age 19.0 ± 0.8 years; height 1.67 ± 0.5 m; weight 59.9 ± 6.7 kg). Descriptive statistics were compared using analysis of variance with repeated measures with a Bonferroni adjustment, and significance was set at p < 0.05. A significant increase occurred after training in the VO2peak (10.5%; p = 0.008), time to fatigue (6.9%; p = 0.017), and interpolated maximal speed (3.6%; p = 0.016), despite there being a decrease in the maximal respiratory exchange ratio (2.9%; p = 0.001). There was no significant change in the RE at 9 km/h; however, there was a significant decrease in the percentage of the VO2peak at 9 km/h (-5.6%; p = 0.02). Maximal isometric strength of knee flexors and extensors did not change. The results suggest a plyometric-agility training program may increase the VO2peak in female soccer players; however, the effect on RE was equivocal.